2012
DOI: 10.1155/2012/698737
|View full text |Cite
|
Sign up to set email alerts
|

Panels Manufactured from Vegetable Fibers: An Alternative Approach for Controlling Noises in Indoor Environments

Abstract: Noise control devices such as panels and barriers, when of high efficiency, generally are of difficult acquisition due to high costs turning in many cases their use impracticable, mainly for limited budget small-sized companies. There is a huge requirement for new acoustic materials that have satisfactory performance, not only under acoustic aspect but also other relevant ones and are of low cost. Vegetable fibers are an alternative solution when used as panels since they promise satisfactory acoustic absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 3 publications
0
14
0
2
Order By: Relevance
“…An example of this is the GMW14177 (15), where a 6.44 m 3 volume chamber is used to take measurements with samples between 0.6 and 2.5 m 2 . Other examples are Hernandez et al (16), where a chamber of 3 m 3 is built and calibrated and samples between 0.4 and 1.4 m 2 are tested, Bradley et al (17), where the chamber volume is 1.71 m 3 and maximum diffusion conditions are requested, or Pacheco et al (18), where the chamber volume is reduced to 0.96 m 3 , the size of samples is 0.3 m 2 and it is used to characterise absorbents based on vegetable fibres, mainly coconut fibres. This paper presents the building and calibration of a small-sized reverberation chamber.…”
Section: Introductionmentioning
confidence: 99%
“…An example of this is the GMW14177 (15), where a 6.44 m 3 volume chamber is used to take measurements with samples between 0.6 and 2.5 m 2 . Other examples are Hernandez et al (16), where a chamber of 3 m 3 is built and calibrated and samples between 0.4 and 1.4 m 2 are tested, Bradley et al (17), where the chamber volume is 1.71 m 3 and maximum diffusion conditions are requested, or Pacheco et al (18), where the chamber volume is reduced to 0.96 m 3 , the size of samples is 0.3 m 2 and it is used to characterise absorbents based on vegetable fibres, mainly coconut fibres. This paper presents the building and calibration of a small-sized reverberation chamber.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that good absorption coefficients which were almost of unity were obtained at a frequency range of 0.8 kHz -1.6 kHz as the density of ferns and baby tears increased. Bastos, de Melo [22] measured coconut, palm, sisal and acai using scaled reverberation chamber. All the four types of vegetable fibres possessed good absorption coefficients of above 0.5 and also passed the flammability, ageing, odour and fungal tests.…”
Section: Introductionmentioning
confidence: 99%
“…The polymer has been widely utilized as a matrix in fiber composites because it is easily formed from a material that has physical and acoustical properties [6][7][8][9][10][11][12][13]. Veerakumar and Selvakumar [6] studied acoustic properties for composite made from kapok fiber with polypropylene fiber, which were found to demonstrate good sound absorption behavior in the frequency range 250-2000 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…Putra et al [10] studied the potential of waste fibers from paddy mixed with polyurethane as 2 Advances in Acoustics and Vibration acoustic material and found that the absorption coefficient is greater than 0.5 from 1 kHz and can reach the average value of 0.8 above 2.5 kHz. Bastos et al [11] developed vegetable fibers: coconut, palm, sisal, and acaı as soundabsorbing panels. Measurement scale reverberation chamber exposed promising results from acoustic performance for all panels.…”
Section: Introductionmentioning
confidence: 99%